Safety of Operation and Maintenance Activities of Rolling Stocks by the Example of Electric Multiple Units EN96 - Artur Kalinowski; Norbert Radek; Jozef Bronček (Communications - Scientific letters of the University of Zilina, 2021)
This paper deals with importance of executing maintenance activities of rolling stocks by the example of the electric multiple unit EN96 series and with influence of repairing rolling stocks on the transport safety. It also discusses Poland’s Supreme Audit Office report for the 2017 year that concerns the condition of safety of the rail transport in Poland. It describes the way in which the maintenance operations are performed with a division of the maintenance levels that depend of time of utilization and distance travelled by a vehicle.